2021
DOI: 10.18632/aging.202523
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate caused behavioral abnormality and neurodegeneration in mice with unilateral nephrectomy

Abstract: Chronic Kidney Disease (CKD) and neurodegenerative diseases are aging-related diseases. CKD with declined renal function is associated with an elevation of circulating indoxyl sulfate, a metabolite synthesized by gut microbes. We explored the roles of gut microbial metabolites in linking with Central Nervous System (CNS) diseases by administrating indoxyl sulfate intraperitoneally to male C57BL/6 mice with unilateral nephrectomy. Upon exposure, the accumulation of indoxyl sulfate was noted in the blood, prefro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 59 publications
0
27
0
1
Order By: Relevance
“…Additionally, another study showed that injection of unilaterally nephrectomized mice with IS significantly increased the levels of the lipid peroxidation indicator malondialdehyde (MDA) in mouse urine and serum. Similarly, significantly decreased levels of antioxidants, including glutathione, SOD-1/SOD-2, and catalase, were detected [ 46 ], indicating that IS may induce oxidative stress by reducing endogenous antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another study showed that injection of unilaterally nephrectomized mice with IS significantly increased the levels of the lipid peroxidation indicator malondialdehyde (MDA) in mouse urine and serum. Similarly, significantly decreased levels of antioxidants, including glutathione, SOD-1/SOD-2, and catalase, were detected [ 46 ], indicating that IS may induce oxidative stress by reducing endogenous antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Marzocco et al indicated that IS has proinflammatory effects on C57BL/6J mice and increases the expression of cox-2 and Bax [ 30 ]. Another study revealed that neuroinflammation [ 46 ], serum IL-1 protein levels, and prefrontal cortical tissue IL-1 mRNA levels are elevated in IS-treated mice. There is no direct evidence or data to allow the comparison of transcriptomic data between IS-treated zebrafish and uremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…These were linked to functional changes of neuronal cells and neuroinflammation. 39 Indoxyl sulfate also induced apoptosis of J o u r n a l P r e -p r o o f astrocytes via oxidative stress and protein kinase inhibition. 40 Indoxyl sulfate administration to rats with CKD impaired cognitive function and BBB integrity via aryl hydrocarbon receptor activation.…”
Section: Indoxyl Sulfatementioning
confidence: 99%
“…In addition, chronically increased IS reduced neurotransmitters such as norepinephrine, serotonin, and dopamine in brainstem, increasing stress sensitivity and lowering locomotor activities, both of which were core characteristics of cognitive frailty [64]. There are also reports identifying IS in cerebrospinal fluids [65]. Nephrectomized mice receiving pCS for 7 weeks exhibit aberrant behavior suggesting cognitive impairment and neuropsychiatric disturbances [66].…”
Section: Protein-bound Utsmentioning
confidence: 99%
“…IS entered central nervous system through the abnormal blood brain barrier with an increased permeability and induced neurobehavioral alterations through binding to the overexpressed AhR in cerebral tissues among CKD rats [67]. Exposure to IS also results in the suppression of neural stem cell activity and a lower level of brain-derived neurotrophic factors (BDNFs), amenable to correction by AhR antagonism [65].…”
Section: Protein-bound Utsmentioning
confidence: 99%